Lithium concentration effect on crystallization kinetics and spectral properties of Cr-doped Li2O-K2O-Al2O3-B2O3 glass-ceramics; Ceramics International; Vol. 49, iss. 12 - Kulpina E. Ekaterina; Babkina A. Anastasiia; Zyryanova K. Ksenia; Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Nuryev R. Rustam; Ignatiev A. Alexander; Zhizhin E. Evgeny; Koroleva A. Aleksandra (2023, 2023)
Title screen